2014
DOI: 10.4081/idr.2014.5627
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hand, foot and mouth disease in the Yucatan Peninsula of Mexico

Abstract: We report a case of hand, foot and mouth disease (HFMD) in a 5-year-old male from Merida City in the Yucatan Peninsula of Mexico. A clinical and physical examination revealed that the patient had symptoms typical of HFMD, including fever, fatigue, odynophagia, throat edema, hyperemia, lesions on the hands and feet, and blisters in the oral cavity. The patient fully recovered after a convalescence period of almost three weeks. Reverse transcription-polymerase chain reaction and nucleotide sequencing revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…Up to nowadays, in the Latin American region, the HFMD has been scarcely studied and few reports shed light about the genetic diversity of the human enteroviruses responsible of outbreaks and sporadic cases of the disease . In concordance with our results, recent reports from Argentina and Brazil have documented HFMD cases linked to CV‐A6, which demonstrates that this type is not only affecting European, Asiatic, and North American children, but also its emergence deserve attention by the public health systems of the Latin American region.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Up to nowadays, in the Latin American region, the HFMD has been scarcely studied and few reports shed light about the genetic diversity of the human enteroviruses responsible of outbreaks and sporadic cases of the disease . In concordance with our results, recent reports from Argentina and Brazil have documented HFMD cases linked to CV‐A6, which demonstrates that this type is not only affecting European, Asiatic, and North American children, but also its emergence deserve attention by the public health systems of the Latin American region.…”
Section: Discussionsupporting
confidence: 89%
“…Back then, authors hypothesized about the role of a CV-A, when isolated a virus from stools and blisters obtained from a 3 years old living in Montevideoboy with symptoms of exanthema vesicular in palms and soles of feet, concomitant with enanthema vesicular in mucosa vestibular. 27Up to nowadays, in the Latin American region, the HFMD has been scarcely studied and few reports shed light about the genetic diversity of the human enteroviruses responsible of outbreaks and sporadic cases of the disease [28][29][30][31][32]. In concordance with our results, recent reports from Argentina and Brazil have documented HFMD cases linked to CV-A6,[30][31][32] which demonstrates that this type is not only affecting European, Asiatic, and North American children, but also its emergence deserve attention by the public health systems of the Latin American region.Different research groups have recently published different proposals for intratypic classification of CV-A6 17,21,33,34 and there is no consensus yet about which one is the most appropriate one.…”
mentioning
confidence: 99%
“…It is important to highlight that although the number of SGDs samples tested in this study is not enough to observe a clear seasonal pattern, results show the transport of NoVs genomes through SGDs during the rainy and dry seasons. Even though EVs have been reported in clinical and environmental samples in Mexico, in concentrations of up to 10 4 GC/L (Espinosa et al, 2009; Gersberg et al, 2006; Machain‐Williams et al, 2014; Sassoubre et al, 2012), our study indicated that the levels of these viruses were below the LoD in all the SGD samples tested. It has been suggested that due to their low persistence in the marine environment, EVs might be better indicators of recent contamination (Futch et al, 2010; Wetz et al, 2004); however, a more intensive spatial–temporal study should be conducted in unique water environments, such as SGDs to test this hypothesis.…”
Section: Discussioncontrasting
confidence: 65%
“…The coverage of HFMD, with the exception of Polar regions, is global in distribution ( Ferson and Bell, 1991 ; Bendig and Fleming, 1996 ; Castro et al, 2005 ; Tu et al, 2007 ; Rabenau et al, 2010 ; Bracho et al, 2011 ; Flett et al, 2012 ; Mirand et al, 2012 ; Kar et al, 2013 ; Machain-Williams et al, 2014 ). The disease is most prevalent in the Asian–Pacific region where it has been endemic since the 1990’s; and has subsequently caused large-scale epidemics every few years ( Ho et al, 1999 ; Komatsu et al, 1999 ; McMinn et al, 1999 ; Fujimoto et al, 2002 ; Lin et al, 2003b ; Tu et al, 2007 ; Sazaly et al, 2009 ; Kim, 2010 ; Wu et al, 2010 ; Tan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%